Pengelolaan Sistem Pembayaran Non Tunai Di Koperasi Sekolah Dasar Islam Terpadu Mujahidul Amin Palangka Raya: Management Of Non-Cash Payment System At The Integrated Islamic Elementary School Cooperative Mujahidul Amin Palangka Raya - Anggi, Anggi; Siminto, Siminto; Irawan, Rio (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The development of digital technology has brought significant changes in various aspects of life, including economic and social. One of the most visible changes is the transformation towards a digital economy, which is now an inevitable choice. Realizing this, the SDIT Mujahidul Amin Cooperative also adopted a non-cash payment system. This research aims to understand the non-cash payment system implemented and how it is implemented. The method used is field research with a descriptive qualitative approach. The object of research is how the application used by the cooperative works. Data is collected through observation, interviews and documentation, then analyzed to reach clear conclusions. The research results show two main findings: first, the SDIT Mujahidul Amin cooperative uses a digital savings-based system through the Ichasoft Pro version 2.6 application, which is also equipped with an RFID Card for digital transactions using NFC Reader technology. Second, the implementation of the digital payment system will begin in 2021 in stages so that students can adapt to this technology. This system was initially implemented to address the problem of students frequently losing money. After considering various solutions, a digital savings application was finally chosen. Using Ichasoft Pro 2.6 has made it easier to manage student cooperatives and transactions, although there are some minor drawbacks, the benefits obtained are very large.